2018
DOI: 10.3762/bjnano.9.252
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mo/Cr bilayer back contacts for thin-film solar cells

Abstract: Molybdenum (Mo) is the most commonly used material as back contact in thin-film solar cells. Adhesion of Mo film to soda–lime glass (SLG) substrate is crucial to the performance of solar cells. In this study, an optimized bilayer structure made of a thin layer of Mo on an ultra-thin chromium (Cr) adhesion layer is used as the back contact for a copper zinc tin sulfide (CZTS) thin-film solar cell on a SLG substrate. DC magnetron sputtering is used for deposition of Mo and Cr films. The conductivity of Mo/Cr bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Indeed, several studies have demonstrated that diffusion occurred between the STS substrate more precisely the steel components (Fe, Cr, Mn, etc.) and the CIGS layer [11,12]. The resistivity values obtained from CIGS layers deposited on glass substrates are in the same range as those reported by Mansour et al [13].…”
Section: Resultssupporting
confidence: 83%
“…Indeed, several studies have demonstrated that diffusion occurred between the STS substrate more precisely the steel components (Fe, Cr, Mn, etc.) and the CIGS layer [11,12]. The resistivity values obtained from CIGS layers deposited on glass substrates are in the same range as those reported by Mansour et al [13].…”
Section: Resultssupporting
confidence: 83%
“…The decrease in reflectance always relates to the increase in surface roughness. 28 The diffuse reflectance of A−F is higher than that of the A−R sample, which indicates that a flatter CZTSe film can be obtained from the precursors with the incorporation of the Cu−Ge layer. For the previous research, the Ge−Se phase will turn into a liquid phase at 380 °C, which could assist grain growth and improve the film quality.…”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, the UV–Vis/DRS data are shown in Figure S4. The decrease in reflectance always relates to the increase in surface roughness . The diffuse reflectance of A–F is higher than that of the A–R sample, which indicates that a flatter CZTSe film can be obtained from the precursors with the incorporation of the Cu–Ge layer.…”
Section: Resultsmentioning
confidence: 94%
“…The deposition of a good ohmic-contact can reduce interface carrier recombination.Thin CuInGeSe or CuZnSnS layer could fail to maintain the high efficiency performance. The main reason behind the poor performance was the substantial drop in short-circuit current density [20][21][22]. The Kesterite photovoltaics that applied for Cu 2 ZnSnS 4 , Cu 2 ZnSnSe 4 , and Cu 2 ZnSn(S 1−x Se x ) 4 emerged as one of the most assured replacements for the chalcopyrite solar cells.…”
mentioning
confidence: 99%